A biomechanical study shoulder pain in elite gymnasts - Cerulli, G.; Caraffa, A.; Ragusa, F.; Pannacci, M. (1998)
Introduction: Shoulder problems are common in overhead sports like baseball, basketball and volleyball. Although gymnastics consists of overhead activities, there are few studies of shoulder problems in this sport. During 1992-1995 we treated five young competitive gymnasts for shoulder pain. Arthroscopy revealed that all suffered from SLAP-lesions or other labral pathologies although they had never dislocated their shoulders. Since four of these athletes stated that they first became aware of acute shoulder pain during ring exercises in suspension, we decided to make an EMG-study of the shoulder musculature during exercises on the parallel bars and rings. Methods: Three elite gymnasts were investigated with telemetric surface EMG of the pect.maj., deltoid, biceps, triceps, trapezius and lat.dorsi. The gymnasts performed the standard bar and ring program. Results: During the ring exercises in suspension there was a `critical phase` during which muscle activity around the shoulder was very low, leading to great articular stresses at the end of the `giant swing`, when their shoulders were suddenly exposed to a load of several times their body weight. EMG of biceps brachii was 67 µV just before the end of the giant swing and increased to 698µV. A similar tenfold increase was found in the other muscles as well. This probably explains the occurrence the SLAP lesions. A very strong pull in the long biceps tendon (before the muscle contracts) could tear loose the superior labrum and cause this socalled SLAP-lesion. Modifications of the rings or the ring exercises might decrease the occurrence of SLAP-lesions. Conclusion: Telemetric EMG analysis of the shoulder musculature during ring exercises provided an explanation for the occurrence of SLAP-lesions in gymnasts.